An Evaluation of the Attractiveness of a Tourist Product (SERVQUAL Method) - Nowacki, Marek (Turyzm/Tourism, 2002)
The article presents an attempt to use the SERVQUAL evaluation method for judging the tourist attractiveness of Rogalin Palace, a branch of the Poznan National Museum. A questionnaire survey was carried out among 102 visitors which pointed to those elements that determined their satisfaction. With the use of a graphic analysis of their expectations and perception, strong and weak points of the attraction were identified.